LANDASAN TAFSIR DAN FIQH IBADAH HAJI PERSPEKTIF ULAMA KLASIK DAN KONTEMPORER - Hamidullah Mahmud; Haina Ash Shabina; Fuzy Wita Astuti; Lola Audina (Jurnal Manajemen Dakwah, 2026)
Hajj is one of the pillars of Islam that encompasses complex spiritual, social, and legal dimensions. The foundations of tafsir and fiqh serve as the primary basis for understanding and implementing the pilgrimage in accordance with the guidance of the Sharia. This study aims to examine the Qur’anic exegesis and hadits related to hajj, as well as to analyze the construction of hajj jurisprudence from both classical and contemporary scholars’ perspectives. The method employed is library research with a thematic approach, connecting Qur’anic verses, Prophetic traditions, and the opinions of jurists across various schools of thought. The findings reveal that the exegesis of hajj verses emphasizes sincerity, patience, and unity of the ummah, while hajj jurisprudence provides a systematic legal framework concerning the pillars, obligations, recommended acts, and prohibitions in performing hajj. The integration of tafsir and fiqh produces a comprehensive understanding that highlights not only ritual aspects but also universal values such as justice, equality, and solidarity. Thus, the foundations of tafsir and fiqh of hajj become an essential basis for shaping a practice of pilgrimage that is both faithful to the Sharia and relevant to the contemporary context of the Muslim community.